Удосконалення вантажних операцій в транспортно-складській системі - Кічкін, Олексій (Видавництво Львівської політехніки, 2015)
Improvement of cargo operations in transport-warehouse systems based on optimization of technical parameters of cargo is presented.
Improvement of cargo operations in transport-warehouse systems